The Drosophila FM7-A Strain Contains a Fixed Translocation Involving the X and 4 Chromosomes. - Maggert, K.; Kindelay, S. (microPublication Biology, 2025)
We discovered that a commonly used balancer chromosome - FM7-A, Tb [1] - exists as an uncharacterized translocation between the progenitor FM7a chromosome and a normal chromosome 4 . Genetic and cytological data evidence show that T (1 ; 4) FM7-A translocates about 5% of chromosome 1 material to an entire chromosome 4 , thus the large "chromosome 1 " segregant is lethal without the small "chromosome 4 " segregant, though the latter is viable and fertile without the former. We characterize this balancer chromosome to inform Drosophila molecular-geneticists of the structure as it may affect their use of this balancer chromosome and the interpretations of their results.